Power, surveillance, and culture in YouTube's digital sphere - Crick, Matthew (Advances in social networking and online communities (ASNOC) book series,, 2016)
This book examines the imaginative, socioeconomic, and innovative features of the video sharing community of YouTube and how these areas traverse the digital world, highlighting theoretical concepts and empirical research, as well as an in-depth discussion on cultural studies, participatory experience, and media theory.